A look at the rational arguments for the abstraction of the human soul from the perspective of Ayatollah Javadi Amoli - Ali Ghadrdangharamaleki; MohamadHasan ghadrdan gharamaleki (حکمت اسرا, 2019)
Self-disclosure is one of the most important issues in psychology, which has a great impact on other issues. Opposite is the view of the inexperience of the soul, which is believed by many scholars. Ayatollah Javadi Amoli, like other scholars and especially followers of transcendent wisdom, believes in the abstraction of the soul, incomplete the view of narrative scholars who defend the physicality of the soul, and uses various rational arguments for this claim. By studying and examining libraries in various works of Ayatollah Javadi Amoli, his views and evidences have been collected and explained by descriptive analysis of these evidences. These arguments are divided into two types: epistemological arguments with the types of "face-to-face science", "study of acquired knowledge by the soul", "perception of generalities" and "union of science, world and known" and non-epistemic with "passion for eternal life" and " The soul, the source of fixed things, can be analyzed. Narrative theologians find these arguments distorted and try to dispute them. The author reflects on these conflicts and responds to them. The evidence for the abstraction of the soul that is included in the works of the predecessors is more than this; But some of them suffer from problems. Ayatollah Javadi Amoli, relying on unfinished arguments, has relied on fully implied arguments. The author believes that in addition to the arguments cited by him, there are other arguments that can prove the abstraction of the soul that Ayatollah Javadi Amoli did not mention.